Importance of nutritional documentation in maintaining health among the elderly - Bugshan, Waleed M.; Balto, Mustafa M.; Almutairi, Munirah A.; Al Awani, Zainab A.; Alenezi, Hana K.; Jawad, Fatima M.; Al Yami, Jaber M.; Sadayo, Tariq Z.; Aljehani, Khalid A.; Alharthi, Yousef O.; Ghazwi, Maryam A. (International Journal Of Community Medicine And Public Health, 2022)
All individuals have a fundamental human right to nutrition. However, it is well known that undernourishment is a common and major health issue among elderly across the globe. Nutritional documentation helps to guarantee correct nutritional care and therapy. Research on medical and nursing home staff's documentation of nutritional care in hospitals and between medical facilities and nursing homes is scarce. The evidence that is presently offered points to unsatisfactory documenting practices. The nursing workforce lacks the necessary skills to appropriately account for the relationship between patients' medical conditions and their nutritional status, as well as the substantial risk of heightened patient suffering brought on by undernutrition. Unsystematic and unorganized recording processes may contribute to the lack of nutritional information document management and sharing. Another challenge is brought on by the inadequate proper nutrition information transfer when elderly patients are transferring between hospitals and nursing facilities. Clarifying roles in nutrition therapy and treatment is part of interprofessional responsibility. The haziness and ambiguity around accountability may be one factor contributing to the lack of attention given to nutritional documentation. Reassessment of the prevailing systems and development an alternate solution way of tracking food consumption among medical and nursing home residents given the present documentation issues, elevated staff turnover rate, and the inability of training and managing interventions to generate long-term behavioral modifications among nursing home staff may aid in reducing the level of undernutrition and lack of nutrition-related documentation among geriatric individuals.